Language Mixing in the Speech of Patani Students in Indonesia - Rosneeda Dadeh; Cece Sobarna; Asri Soraya Afsari (Eduvest - Journal of Universal Studies, 2026)
The phenomenon of code mixing among multilingual speakers reflects complex dynamics of language, identity, and social adaptation. This study discusses the phenomenon of code mixing carried out by Thai speakers, particularly Patani students living in Indonesia, with a focus on the use of Patani Malay in their daily interactions. This study aims to identify the factors that affect the occurrence of code-mixing using theories from Asmah Haji Omar (1985, 1992) and Fishman (1972). The data was obtained through videos of Patani students in Indonesia. Analysis of nine speeches showed that the practice of mixing code was influenced by factors of group identity, social solidarity, communicative situation, and domain of language use. The analysis of nine speeches showed that the practice of code mixing was influenced by factors of group identity, social solidarity, communicative situation, and domain of language use. The dominant form of code mixing found was lexical code mixing, where Patani Malay words such as gapo, paehae, sain, kecek, bedey, and sutey-sutey were inserted into Indonesian sentences. The results of this study show that Patani Malay is used not only as a means of communication but also as a marker of ethnic identity and solidarity among Patani students in the midst of a multilingual environment such as Indonesia. This code-mixing phenomenon reflects linguistic resilience and efforts to maintain cultural identity in diaspora contexts.